Validation of Educational Robotic-Based Work and Energy Learning Module using Structured Inquiry Model to Improve Students’ Concept Comprehension - Astri Juwita Siregar; Wawan Kurniawan; Cicyn Riantoni; Hebat Shidow Falah (Universitas Muhammadiyah Enrekang, 2025)
Students' poor understanding of the concepts of work and energy leads to students' difficulties in connecting theory to practice, as well as students' lack of ability to apply the concepts of work and energy in problem solving. In addition, the use of robotic technology can increase student involvement in the learning process and help students understand abstract concepts through practical experience. This development aims to produce a product in the form of an Educational Robotics-based Work and Energy learning module using a Structured Inquiry model as a solution to these problems. The purpose of this research is to determine the initial study and validity of the module. The development model used is the ADDIE development model. The data analysis technique used is the spiral method and quantitative descriptive statistical analysis. Based on the data analysed, there are two research findings. Firstly, interviews were conducted with educators at the needs analysis stage. Secondly, the results of validation by media experts were 87,05% with a very valid category and the results of validation by material experts were 90,35% with a very valid category. The results of this study conclude that the Educational Robotics-based Work and Energy learning module with the Structured Inquiry model is valid for use in learning.